2008
DOI: 10.1038/ng.240
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility loci for intracranial aneurysm in European and Japanese populations

Abstract: Stroke is the world’s third leading cause of death. One cause of stroke, intracranial aneurysm, affects ~2% of the population and accounts for 500,000 hemorrhagic strokes annually in midlife (median age 50), most often resulting in death or severe neurological impairment1. The pathogenesis of intracranial aneurysm is unknown, and because catastrophic hemorrhage is commonly the first sign of disease, early identification is essential. We carried out a multistage genome-wide association study (GWAS) of Finnish, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
230
3
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(242 citation statements)
references
References 30 publications
(44 reference statements)
6
230
3
3
Order By: Relevance
“…In our study, we tested for association between the three SNPs and IA at the first stage of the current GWAS (194 IA cases and 288 controls) and obtained ORs and 95% CIs for the SNPs as follows: rs1429412, OR¼1.13 (95% CI, 0.79-1.33); rs10958409, 1.20 (0.78-1.53); and rs1333040, 1.29 (0.98-1.72). The ORs were not so different from those in the previous study, 11 but the effect sizes showed no statistical significance. This GWAS has limited power to detect loci with small effect sizes (for example, o10% power to detect common variants with genotypic relative risk of 1.3; also see Supplementary Figure 1).…”
Section: Gwas For Intracranial Aneurysmcontrasting
confidence: 82%
See 3 more Smart Citations
“…In our study, we tested for association between the three SNPs and IA at the first stage of the current GWAS (194 IA cases and 288 controls) and obtained ORs and 95% CIs for the SNPs as follows: rs1429412, OR¼1.13 (95% CI, 0.79-1.33); rs10958409, 1.20 (0.78-1.53); and rs1333040, 1.29 (0.98-1.72). The ORs were not so different from those in the previous study, 11 but the effect sizes showed no statistical significance. This GWAS has limited power to detect loci with small effect sizes (for example, o10% power to detect common variants with genotypic relative risk of 1.3; also see Supplementary Figure 1).…”
Section: Gwas For Intracranial Aneurysmcontrasting
confidence: 82%
“…Because Bilguvar et al 11 have replicated three SNPs significantly associated with IA by using a subset of our Japanese cohort (rs1429412 on chromosome 2q, rs10958409 on chromosome 8q and rs1333040 on chromosome 9p in 495 IA cases and 676 non-IA controls), the SNPs are likely to be true positives. In our study, we tested for association between the three SNPs and IA at the first stage of the current GWAS (194 IA cases and 288 controls) and obtained ORs and 95% CIs for the SNPs as follows: rs1429412, OR¼1.13 (95% CI, 0.79-1.33); rs10958409, 1.20 (0.78-1.53); and rs1333040, 1.29 (0.98-1.72).…”
Section: Gwas For Intracranial Aneurysmmentioning
confidence: 96%
See 2 more Smart Citations
“…Although several common variants were identified to be associated with the increased risk of IA development through candidate gene approaches [12][13][14][15][16] and genome-wide association studies, 17,18 only few associations were consistently replicated. 19,20 These might be because of the lack of statistical power of the study or differences in the allele frequencies across different populations.…”
Section: Introductionmentioning
confidence: 99%